Geology of the Dyer Mountain quadrangle, Utah - Patch, Nickolas Lee (Kansas State University, 2009)
The Dyer Mountain quadrangle, located in Utah approximately 200 km east of Salt Lake City and 20 km north of Vernal, lies on the south flank of the east-west trending Uinta anticline. The topography of the area varies from mountain peaks to deep canyons, with rolling hills of uplands in between. The elevation in the quadrangle ranges from 3124 m (10248 ft) at the top of Dyer Mountain to 1835 m (6020 ft) at the lowest point of Big Brush Creek. Most of the northern portion of the quadrangle is vegetated by aspens and pines, whereas the southern part of the quadrangle is covered with sagebrush and grasses. Due to its location on the anticline, the quadrangle contains bedrock that dips gently to the south and southeast. The ages of the rocks within the quadrangle range from the Precambrian Uinta Mountain Group to the Quaternary and Tertiary gravels. Also present are the following formations: Cambrian Lodore; Mississippian Madison, Doughnut, and Humbug; Pennsylvanian Round Valley and Morgan; Pennsylvanian to Permian Weber; Permian Meade Peak Member of the Phosphoria and Franson Member of the Park City; and various Quaternary sediments. The Lodore Formation and the Madison Limestone rest on major unconformities, and the Quaternary and Tertiary gravels overlie the Gilbert Peak erosion surface. The Uinta anticline and southerly dip of the Proterozoic and Paleozoic rocks are a result of Late Cretaceous uplift during the Laramide orogeny; Tertiary rocks within the area show little to no deformation. Limestone and various types of ores have been mined in the quadrangle, and phosphorous is currently being mined for fertilizer production. Several landslides, common at the juncture of the Quaternary and Tertiary gravels and Permian shales, were identified within the quadrangle. An anticline and syncline, trending northwest to southeast, lie in the southeast portion of the quadrangle and transect Big Brush Gorge. Geologic hazards of the area include landslides, erosion and failure of road grades, and cliffs near trails. The karst topography of the area presents dangers of sink holes, and evidence of ceiling collapse is present within Big Brush Cave, a popular destination for tourists and cavers.
Keywords: Dyer Mountain quadrangle; Utah geology; Geologic mapping; Geology (0372)